The effect of excessive confidence, optimism, and herd behavior on the investment decision-making process - an applied study in the Iraqi stock market - Maitham Rabee Hadi Al-Hasnawi; Ali Ahmed Faris (Iraqi Journal for Administrative Sciences, 2025)
The analysis and interpretation of changes in asset prices in financial markets, has adopted a long period of time on the theories of traditional financial adopting assumptions that rational investors in these markets and the difficulty of achieving abnormal profits or superiority in the market in light of the availability of information to all and uniformity in the interpretation of this information by investors . But the new entrance in a financial behavioral finance has proved not as rational investors like traditional financial say and there are many deviations from rational behavior to them when making the decision because of the suffering of some of the cognitive and psychological biases that affect the decision-making process. Hence the study was based on the problem represented investors in the stock markets suffering from cognitive biases that may lead them to increases the risk when they making decisions without adequate compensation for the return. The study tried to show the role played by biases overconfidence and herd behavior and Over optimism in the decision- making process for investors in the stock market. The study adopted a questionnaire to measure these biases and conducted on a sample of investors in the Iraqi's stock exchange amounted to 107 from investors. Statistical methods were used to help the researcher to detect the presence of these biases and their impact on the decision-making process. The study found that excessive confidence and herd behavior and excessive optimism statistically significant effect on the decision-making process dimensions consisting of trading volume and the level of diversification and the attitude toward risk.